Pengaruh Cekaman Kekeringan Terhadap Pertumbuhan, Hasil dan Kandungan Prolina Daun Cabai - Yusniwati Yusniwati; Sudarsono Sudarsono; Hajrial Aswidinnoor; Sri Hendrastuti; Djoko Santoso (Jurnal Agrista, 2008)
Drought Stress Effect on Growth, Yield and Leaf Proline Accumulation of Hot PepperABSTRACT. The objective of this experiment were to evaluate effects of drought stress at vegetative stage on growth, yield and leaf proline content of hot pepper. Drought stress was conditioned by reduction watering of crop show wilt symptom 70% during the period of 21 – 54 days after planting (DAP). Result of the experiment indicated that drought stress reduced plant height, branch number, stem, diameter, root length, shoot, root, and biomass dry weight and fruit yield. Sensivity index calculated based on biomass of five hot pepper cultivars showed that Prabu, laris, dan jati laba were the medium tolerance to drought stress. There was no drought tolerance cultivar if the sensivity index was calculated based on fruit yield.